Epigenomic Modifications Mediating Antibody Maturation - Sheppard, Emily C.; Morrish, Rikke Brandstrup; Dillon, Michael J.; Leyland, Rebecca; Chahwan, Richard (Frontiers in Immunology, 2018)
Epigenetic modifications, such as histone modifications, DNA methylation status, and non-coding RNAs (ncRNA), all contribute to antibody maturation during somatic hypermutation (SHM) and class-switch recombination (CSR). Histone modifications alter the chromatin landscape and, together with DNA primary and tertiary structures, they help recruit Activation-Induced Cytidine Deaminase (AID) to the immunoglobulin (Ig) locus. AID is a potent DNA mutator, which catalyzes cytosine-to-uracil deamination on single-stranded DNA to create U:G mismatches. It has been shown that alternate chromatin modifications, in concert with ncRNAs and potentially DNA methylation, regulate AID recruitment and stabilize DNA repair factors. We, hereby, assess the combination of these distinct modifications and discuss how they contribute to initiating differential DNA repair pathways at the Ig locus, which ultimately leads to enhanced antibody–antigen binding affinity (SHM) or antibody isotype switching (CSR). We will also highlight how misregulation of epigenomic regulation during DNA repair can compromise antibody development and lead to a number of immunological syndromes and cancer.